Unhealthy lifestyle and sleep problems as risk factors for increased direct employers’ cost of short-term sickness absence - Kanerva, Noora; Pietiläinen, Olli; Lallukka, Tea; Rahkonen, Ossi; Lahti, Jouni (Scandinavian Journal of Work, Environment & Health, 2018)
' ' OBJECTIVES ': 'Unhealthy lifestyle (eg, smoking) as well as sleep problems are associated with increased risk of sickness absence, but the financial impact of these associations beyond risk ratios is not well known. We aimed to estimate the additive contribution of lifestyle and sleep problems (risk factors) to direct costs of short-term (<15 days) sickness absence. ' ' METHODS ': 'The Helsinki Health Study is a longitudinal cohort of employees of the City of Helsinki, Finland (N=8960, response rate 67%). During 2000–2002 the participants were mailed a survey questionnaire that gathered information on their lifestyle and sleep. A sum of the risk factors was calculated: participants received one point for being a smoker; high alcohol user (>7 servings/week for women and >14 servings/week for men); physically inactive [<14 metabolic equivalents (MET) hours/week]; having low fruit and vegetable consumption (<1 times/day); or suffering from frequent insomnia symptoms. Sickness absence, salary, and time of employment were followed through the employer’s register between 2002–2016. Individual salary data were used to calculate the direct costs of short-term sickness absence. Data were analyzed using a two-part model. ' ' RESULTS ': 'Direct costs of short-term sickness absences were on average €9057 (standard deviation €11 858) per employee over the follow-up. Those with ≥3 risk factors had €3266 [95% confidence interval (95% CI) €2114–4417] higher direct costs for the employer over the follow-up compared to those without any risk factors. ' ' CONCLUSIONS ': 'Unhealthy lifestyle and sleep problems may increase the costs of short-term sickness absence to the employer by 10–30%. Consequently, programs addressing lifestyle and sleep may yield to significant savings.
Keywords: alcohol; cost; employer cost; fruit; Helsinki Health Study; insomnia symptom; lifestyle; physical activity; risk factor; short-term sickness absence; sick leave; sickness absence; sleep; sleep duration; sleep problem; smoking; unhealthy lifestyle; vegetable